2009
DOI: 10.1111/j.1365-2753.2008.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative anxiety and depression levels in orthopaedic surgery: a study of 56 patients undergoing hip or knee arthroplasty

Abstract: The results suggest that post-operative depression does occur in orthopaedic surgery. The prevalence may be higher than that reported in other surgical specialities. These findings emphasize the need for evaluation of patients' psychiatric state post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 16 publications
(25 reference statements)
2
46
2
2
Order By: Relevance
“…The prevalence of extreme/major depression in total female (46.6%) was higher as compared to total male (25.7%) which is in agreement with Nickinson RS et al (2009) 17 who reported that females were more likely to become depressed than males while Crichlow RJ et al (2006) 9 observed that the prevalence of clinically relevant depression approached 45% in a diverse cohort of orthopaedic trauma patients. Socio-economic status and ortho illness was highlighted with strong association (p<0.001) with depression.…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of extreme/major depression in total female (46.6%) was higher as compared to total male (25.7%) which is in agreement with Nickinson RS et al (2009) 17 who reported that females were more likely to become depressed than males while Crichlow RJ et al (2006) 9 observed that the prevalence of clinically relevant depression approached 45% in a diverse cohort of orthopaedic trauma patients. Socio-economic status and ortho illness was highlighted with strong association (p<0.001) with depression.…”
Section: Discussionsupporting
confidence: 78%
“…In the immediate postoperative period, the rate of depression has been reported to be between 21 and 50% in study populations with low (0–11.8%) levels of preoperative depression. Indeed, postoperative pain intensity is correlated with the degree of depressive symptoms [13]. High postoperative depression scores have also been associated with increased length of stay and poor functional outcomes after surgeries [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…As in the present study, Nickinson et al [32] found a correlation between postoperative anxiety levels and length of hospital stay, but the study of Nickinson investigated patients undergoing knee or hip arthroplasty, whose mean for the group who were anxious was 5 days versus 4 days for the group that did not show anxiety. Thus, it is thought that an appropriate intervention in order to reduce the anxiety levels of patients undergoing surgical procedures has not only clinical outcomes but also a reduction in costs generated by the reduction in length of hospital stay.…”
Section: Discussionmentioning
confidence: 55%